Adolescents’ Mindfulness and Psychological Distress: The Mediating Role of Emotion Regulation - Ma, Ying; Fang, Siqi (Frontiers in Psychology, 2019)
Mindfulness has been widely linked with psychological well-being in general population. There are emerging studies supporting the relationship between adolescents’ mindfulness and their mental health. However, the mechanisms through which mindfulness may influence adolescents’ psychological distress have only recently been explored, and more related research is still needed. This study investigated the relationship between adolescents’ dispositional mindfulness and psychological symptoms of depression, anxiety and stress. The mediating variables were also explored in perspective of two common emotion regulation theories, which were measured through Difficulties in Emotion Regulation Scale (DERS) and Emotion Regulation Questionnaire (ERQ). DERS has been used as a comprehensive assessment of emotion regulation difficulties. ERQ is also widely accepted to measure the emotion regulation process including dimensions of cognitive reappraisal and expressive suppression. Measures assessing mindfulness, emotion regulation, and psychological distress were administered to 1067 adolescents in mainland China. The results confirmed that adolescents’ dispositional mindfulness was negatively associated with depression, anxiety, and stress. DERS, especially the sub-dimensions of Acceptance and Strategies, significantly mediated the relationship between mindfulness and symptoms of depression, anxiety and stress. Whereas, ERQ including subscales of cognitive reappraisal and expressive suppression exerted limited mediating effect. These findings provided insights for the potential underlying mechanism between adolescents’ mindfulness and psychological distress, demonstrating that DERS might be more pervasive than ERQ. Further research was suggested to explore other mediating variables underlying mindfulness and psychological distress among adolescents and develop mindfulness-based programs to improve adolescents’ mindfulness and emotion regulation ability.